2006
DOI: 10.1143/jpsj.75.054003
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Integrals and Several Integrable Differential-Difference Systems

Abstract: In this paper, the relations between three special forms of matrix integrals and their associated integrable differential-difference systems are considered. It turns out that these matrix integrals with special β = 2 and 1, 4 satisfy the differential-difference KP equation, the two-dimensional Toda lattice, the semi-discrete Toda equation and their Pfaffianized systems, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…As pointed out by Kakei in [12], once written in that form, the integrals in (1.2) in the cases β = 1, 2 can be interpreted as the continuum limits of N -soliton solutions. It can also be verified that the same observation applies to the integrals (1.3) studied in [18]. It is interesting to note that Tracy and Widom [3] used the identities (1.4), (1.5), and (1.6), to obtain Fredholm determinant expressions for expressions involved in the study of the spacings between consecutive eigenvalues.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…As pointed out by Kakei in [12], once written in that form, the integrals in (1.2) in the cases β = 1, 2 can be interpreted as the continuum limits of N -soliton solutions. It can also be verified that the same observation applies to the integrals (1.3) studied in [18]. It is interesting to note that Tracy and Widom [3] used the identities (1.4), (1.5), and (1.6), to obtain Fredholm determinant expressions for expressions involved in the study of the spacings between consecutive eigenvalues.…”
Section: Introductionmentioning
confidence: 62%
“…This connection of (1.1) with integrable systems was deepened by the authors of [18] who introduced dependence on the continuous variables t 1 , t 2 , and s and the discrete variables n 1 and n 2 in the following way…”
Section: Introductionmentioning
confidence: 99%
“…Matrix integral solutions (II). As was shown in [10,12], the partition function of the symplectic ensemble can also play a role as the tau function of the Pfaffianized system. Therefore, let's consider the case β = 4 with regarding to the equation (1.1).…”
Section: Matrix Integral Solutions (I)mentioning
confidence: 80%
“…The discrete integrable systems also play important roles in integrable theory and their connections with matrix models are interesting to be discussed. For example, in [12], the matrix integral solutions of several integrable differential-difference systems were considered, whose tau functions were shown to be related to the integrals of the eigenvalues in the form…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the time-dependent partition functions of matrix models provide us some explanations for integrable hierarchies. It has been realised that the partition function of coupled two-matrix models could be regarded as the tau function of 2d-Toda hierarchy [3], and the partition function of symplectic ensemble and orthogonal ensemble could be regarded as the tau functions of Pfaff lattice and some differential-difference equations [4,7,21]. It is also found that the partition function of Bures ensemble could be viewed as the tau function of BKP hierarchy [22,31] and that of Cauchy two-matrix model is related to the CKP hierarchy [26].…”
Section: Introductionmentioning
confidence: 99%